Polysialic Acid Directs Tumor Cell Growth by Controlling Heterophilic Neural Cell Adhesion Molecule Interactions - Seidenfaden, Ralph (American Society for Microbiology, 2003)
Polysialic acid (PSA), a carbohydrate polymer attached to the neural cell adhesion molecule (NCAM), promotes neural plasticity and tumor malignancy, but its mode of action is controversial. Here we establish that PSA controls tumor cell growth and differentiation by interfering with NCAM signaling at cell-cell contacts. Interactions between cells with different PSA and NCAM expression profiles were initiated by enzymatic removal of PSA and by ectopic expression of NCAM or PSA-NCAM. Removal of PSA from the cell surface led to reduced proliferation and activated extracellular signal-regulated kinase (ERK), inducing enhanced survival and neuronal differentiation of neuroblastoma cells. Blocking with an NCAM-specific peptide prevented these effects. Combinatorial transinteraction studies with cells and membranes with different PSA and NCAM phenotypes revealed that heterophilic NCAM binding mimics the cellular responses to PSA removal. In conclusion, our data demonstrate that PSA masks heterophilic NCAM signals, having a direct impact on tumor cell growth. This provides a mechanism for how PSA may promote the genesis and progression of highly aggressive PSA-NCAM-positive tumors.